THE EFFECTIVENESS OF UMMI METHOD IN ENHANCING GHARIB AND TAJWID SKILLS: A QUASI-EXPERIMENTAL STUDY AT TPQ NURUL JADID PASURUAN - Nanda Ni'matul Nabilla; Khoirun Nasihin (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
This study examines the effectiveness of the Ummi Method in improving students' gharib (rare Qur'anic readings that deviate from general rules) and tajwid (rules of Qur'anic pronunciation) skills at TPQ Nurul Jadid Winongan Pasuruan. Qur'anic learning at TPQ often faces challenges in teaching these two crucial components. The Ummi Method presents a structured learning system with emphasis on direct method, repetition, and direct correction. This quasi-experimental research employed a pretest-posttest control group design with 72 students divided into experimental and control groups. Data collection included observation, in-depth interviews, documentation, and standardized reading assessments. The findings reveal that: (1) the Ummi Method implementation followed five standard stages: murojaah, talqin (imitation), individual reading-listening, direct correction, and evaluation; (2) the experimental group showed significantly higher post-test scores in both tajwid (M=82.8, SD=3.5) and gharib (M=76.2, SD=4.1) compared to the control group (tajwid M=78.4, SD=4.7; gharib M=71.2, SD=5.3), with t-test results indicating significant differences at p<0.05; (3) the Ummi Method proved effective in improving both skills, evidenced by tajwid score increase from 72.5 to 82.8 (experimental group), gharib score increase from 65.0 to 76.2, and effect size (Cohen's d) of 1.04 for tajwid and 1.16 for gharib. This research contributes empirically to the effectiveness of the Ummi Method in Qur'anic education and provides practical implications for TPQ institutions in improving the quality of Qur'anic reading instruction. This research contributes to the literature on Qur'anic education by providing comprehensive empirical evidence of the Ummi Method's effectiveness in improving both gharib and tajwid skills simultaneously.